Epilepsy as a systemic condition: Link with somatic comorbidities. (1st June 2017) - Novy, J.; Bell, G. S.; Peacock, J. L.; Sisodiya, S. M.; Sander, J. W.
Abstract : Background: People with epilepsy have more concomitant medical conditions than the general population; these comorbidities play an important role in premature mortality. We sought to generate explanatory hypotheses about the co‐occurrence of somatic comorbidities and epilepsy, avoiding causal and treatment‐resultant biases. Methods: We collected clinical, demographic and somatic comorbidity data for 2016 consecutive adults with epilepsy undergoing assessment at a tertiary centre and in 1278 people with epilepsy in the community. Underlying causes of epilepsy were not classed as comorbidities. Results: Somatic comorbidities were more frequent in the referral centre (49%) where people more frequently had active epilepsy than in the community (36%). Consistent risk factors for comorbidities were found in both cohorts. Using multivariable ordinal regression adjusted for age, longer epilepsy duration and an underlying brain lesion were independently associated with a smaller burden of somatic conditions. The treatment burden, measured by the number of drugs to which people were exposed, was not an independent predictor. Shorter epilepsy duration was a predictor for conditions that conceivably harbour significant mortality risks. Conclusions: Somatic comorbidities do not occur randomly in relation to epilepsy; having more severe epilepsy seems to be a risk factor. Independently from age, the early period after epilepsy onset appears to be at particular risk, although it is not clear whether this relates to an early mortality or to a later decrease in the burden of comorbidities. These results suggest that, for some people, epilepsy should be considered a systemic condition not limited to the CNS.